Does the pattern of repeated sprint ability differ between sickle cell trait carriers and healthy subjects? - Connes, P.; Racinais, S.; Sara, F.; Marlin, L.; Hertogh, C.; Saint-Martin, C.; Etienne-Julan, M.; Hue, O. (International Journal of Sports Medicine, 2006)
Sickle cell trait (SCT) is a genetic abnormality affecting the synthesis of normal haemoglobin [Hb] and is the heterozygous form of sickle cell anaemia. The aim of the present study was to compare the ability to repeat maximal cycling sprints (RSA; repeated sprint ability) between SCT carriers (SCT group, n = 7) and a control group with normal haemoglobin [Hb] (n = 7). The two groups performed a 10-s maximal cycling sprint in order to determine the peak power output (Ppeak10). They then performed an RSA test that consisted of five 6-s maximal cycling sprints interspersed with 24 s of passive recovery. For each sprint, the peak power output (Ppeak6) and the work over the 6-s (W6) were calculated. The sum of each W6 developed during the test was considered to be the total work (Wtot). The decrements over the repeated sprints for Ppeak6 (P6dec) and W6 (W6dec) were also determined. We found no difference in Ppeak10, Wtot and W6dec between the two groups. However, the drop in Ppeak6 and W6 during the RSA test appeared earlier in the SCT group and the decrease in Ppeak6 over the RSA test was greater in the SCT group than in the control group (p < 0.05). In conclusion, we found that: 1) maximal anaerobic performance determined during a single sprint was not altered by SCT, but 2) repeated sprint ability was different in SCT carriers compared with sportsmen with normal Hb.